Answer:y=-6
Step-by-step explanation:
-3(2)
bro where is the pic???? how are we supposed to answer this?
Answer:
StartFraction 6 Over 5 x Superscript 10 Baseline EndFraction
Step-by-step explanation:
Apparently you want to simplify ...
The applicable rules of exponents are ...
(a^b)(a^c) = a^(b+c)
1/a^b = a^-b
(a^b)^c = a^(bc)
__
So the expression simplifies as ...
This can be solved by Newton's binomial formula
Tk+1 = (n k) a∧(n-k) b∧k k+1=7 => k=6, n=11 , a=-3x and b=-2y
T7= (11 6) (-3x)∧(11-6) (-2y)∧6 = (11*10*9*8*7)/(1*2*3*4*5) (-3x)∧5 (-2y)∧6
T7= 462 (-3x)∧5 (-2y)∧6
The correct answer is A.
Good luck!!!